Factors affecting job satisfaction of lecturers- evidence from Vietnamese universities - Bui, Ngoc Thi (Archives of Business Research, 2019)
The quality of training is an important issue and is of special concern to universities. Lecturers has a pioneering role in innovation of higher education management since the quality of higher education is always associated with the quality of lecturers. Assessing job satisfaction of lecturers is a fundamental step for universities to improve quality and job satisfaction of lecturers as well as attract and retain qualified lecturers. This study aims at assessing job satisfaction of lecturers in Vietnamese universities. For the purpose of this study, quantitative research method was applied. The questionnaires were sent randomly to 131 lecturers from 48 universities in Vietnam via email and google doc. Then, data was analyzed by various tool including descriptive statistics, frequency, exploratory factor analysis and multiple regression analysis. The study examined four factors affecting lecturer job satisfaction include Facilities, Job Characteristics, Salaries and Fringe Benefits, Development Opportunities. Specifically, Job Characteristics have the strongest impact on lecturer job satisfaction while Salary and Fringe Benefits have the smallest impact on lecturer job satisfaction. The research on factors affecting job satisfaction of lecturers helps universities to develop appropriate policies in order to maintain and develop lecturers, as well as attract talents and prevent the “brain drain”.